Development of a model of an electrical complex for gas air cooling devices of gas field №1 gazprom dobycha Yamburg LLC with a centralized power supply system in the MATLAB/SIMULINK program - L. R. Maskov; V. Y. Kornilov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To develop a model in MATLAB/SIMULINK environment for the system of mechatronic movement modules (MMD) of the electrical complex, which includes gas air coolers with centralized system of power supply of the gas field 1 of "Gazprom dobycha Yamburg" LLC. To analyze the energy efficiency of MMD ETC ACHE. To perform the experimental research of the EMD EMD ETC ACHE model in the dynamic modes in order to determine the regularity of the influence of single (group) starts on the power supply source overload. To develop a switching algorithm for MMD ETK AHE at direct starts of asynchronous motors (AD), providing restoration of the technological mode within the optimum time after the voltage disappearance for the centralized power supply system.METHODS. The results presented in work are received with use of methods of the theory of electric and magnetic circuits, the theory of electric drive and electric machines, methods of optimization of power supply systems, analytical and numerical methods of applied mathematics, methods of mathematical and computer modeling.RESULTS. In article urgency of a theme is described, features of construction and modelling of ETK GP in the environment MATLAB/SIMULINK with the centralized system of power supply are considered. The comparative analysis of existing methods and calculation of parameters of the substitution schemes of the MMD ETK GP was carried out. Approximate calculation of mechanical and inertial characteristics for creating a model of load (resistance moment) for the motor. The model of EMD of electric motor drive compressor unit was created, as close as possible to the real existing system on the basis of catalog (passport) data of individual elements of electric motor drive unit. There were analyzed and developed proposals to enhance power efficiency of EMD ETC AHE and algorithms, which provide optimal direct start-up of the AHE fan group within the set time after the power failure without overloading of the power supply source, were proposed.CONCLUSIONS. On the basis of results of computer modeling, the peculiarities of operation of EMD ETH ACHE, which require further study and development of corrective measures to improve energy efficiency and reliability of power supply system of GP. Combination of direct starts of single (group) fans of ACHE, obtained at this stage of research of EMD EMD ETC ACHE model, will create the basis (algorithm) for automated control system of this complex, which will ensure restoration of technological mode within optimum time after power outage without overloading of centralized power supply source. Calculation of parameters of individual elements of MMD model of ETC AVO will allow to use data to create other models of ETC GP, which will allow to conduct in-depth research and improve the energy efficiency of the entire system of power supply of GP.